An ex post facto study of critical thinking skills in mathematics learning based on school geography - Nurhikmayati, Iik; Priatna, Nanang; Dahlan, Jarnawi Afgani; Minasyan, Sona (Universitas Islam Raden Intan Lampung, INDONESIA, 2024)
Background: Educational disparities in Indonesia necessitate a comprehensive evaluation of students' critical thinking skills across various geographical regions, including highlands, border areas, and lowlands, to address potential educational shortcomings.Aim: The study aims to quantitatively assess and compare the mathematical critical thinking abilities of junior high school students across different geographical settings to inform educational strategies and interventions.Method: Employing a quantitative approach with an ex post facto causal comparative research design, the study utilized cluster sampling to select a representative sample of 82 students from highland, border, and lowland schools. Descriptive and inferential statistical analyses, including Kruskal-Wallis tests and post hoc examinations, were conducted to analyze the data.Result: Preliminary descriptive analysis indicated a general lack of critical thinking skills in mathematics among students in all areas. However, inferential statistical analysis revealed significant differences in the critical thinking abilities of students from the three geographical regions, with students in urban (lowland) areas displaying superior critical thinking rankings compared to their counterparts in border and rural (highland) areas.Conclusion: The findings underscore significant geographical disparities in mathematical critical thinking skills among Indonesian junior high school students. These disparities are likely influenced by factors such as unequal access to educational resources, teaching methodologies, student interest, and the socioeconomic and educational backgrounds of parents. Addressing these inequalities is crucial for enhancing the educational outcomes and critical thinking abilities of students across Indonesia.